IDENTIFICATION OF DROUGHT TOLERANT GENOTYPES OF BARLEY (HORDEUM VULGARE L.) THROUGH STRESS TOLERANCE INDICES - G. M. Subhani; Abdullah; J. Ahmad; J. Anwar; M. Hussain; A. Mahmood (Journal of Animal and Plant Sciences, 2015)
Stress tolerance indices viz tolerance index (TOL), mean productivity (MP), stress susceptibility index (SSI), geometric mean productivity (GMP), stress tolerance index (STI), yield stability index (YSI), yield index (YI), etc., were used to evaluate genotypes with high yield and drought tolerance. The barley line B-09006 produced highest yield under irrigated conditions but could not perform well under drought stress conditions. The lines B-09008, B-09005, B-09003 and B-09023 gave comparable yield under irrigated conditions but highest yield under stress conditions. These have highest values of MP, GMP and STI so these lines have high stress tolerance and yield potential. The highest Ys, MP, GMP, YI and STI were recorded in B-09008 line, followed by B-09003. Yp had positive and significant correlation with MP, GMP and STI while Ys had significant and positive correlation with all stress indices except TOL and SSI. First principal component analysis (PCA) contributed 76.9% of the variation with Yp, Ys, MP, GMP, STI and YI. Thus the first component can be named as the yield potential and drought tolerance while second PCA explained 22.8% of the total variability. B-09008, B-09003, B09005 and B-09026 were more suitable and stable genotypes for irrigated and drought stress conditions.
Keywords: barley; stress tolerance indices; principle component analysis